PENGARUH PEMBERIAN SALEP EKSTRAK KUNYIT KUNING (Curcuma longa Linn) TERHADAP PENYEMBUHAN LUKA SAYAT PADA TIKUS PUTIH (Rattus norvegicus) - Muthia Milasari; Abdul Wahid Jamaluddin; Yuko Mulyono Adikurniawan (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Turmeric is one of the herbal contents substancials that believed help wound healing process. Scientifically, turmeric has been shown to have an anti-inflammatory and choleretic effect. The curcumin compound has potential effects as antimicrobial and antioxidant that can accelerate the re-epithelialization and migration of cells such as myofibroblast, fibroblasts and macrophages. Those are compounds for wound healing. The aims of this study is to know the effect of yellow tumeric extract oinment in wound healing based on the time of wound close and morphological changes are compared with the controls. This study was carried out by experimental test. The experimental animals were divided into 5 groups, each group consisted of 5 animals. Each group is treated, among others by giving 10%, 20%, and 30% yellow turmeric extract ointment (treatment groups), povidone iodine 10% ointment (positive control) and ointment base (negative control). The rats were given an incision in the back of the vertebrae with square pattern around ±2cm to fascia. Yellow turmeric extract ointment was applied to rat wounds 2 times a day and observed daily from day 1 to day 14. Data were analyzed using ANOVA (analysis of variance). The results showed a significant difference in 5 groups (P< 0.05). There were differences in the results of the study between the treatment group (10%, 20% and 30% yellow tumeric extract ointment), positive control (povidone iodine 10% ointment) and negative control group (ointment base) which showed a faster treatment group to heal wounds compared the control group. The study reveals that 10% yellow turmeric extract ointment is best in accelerating wound healing.